Effects of Libyan Balanites aegyptiaca Extract on Steroid Hormone Levels in Male Rabbits - Fayrouz Khaled; Sultana Hussien; Rabihah Mahmoud; Najwa Belhamad (Khalij-Libya Journal of Dental and Medical Research, 2025)
Balanites aegyptiaca, commonly known as the desert date or Heglig, is a multifunctional tree native to arid and semi-arid regions of Africa and the Middle East, including Libya. Traditionally, it has been used to treat diabetes, liver disorders, skin infections, and reproductive problems due to its rich content of bioactive compounds such as flavonoids, saponins, alkaloids, and phenolic compounds. Phytochemical studies indicate that steroidal saponins in B. aegyptiaca are structurally similar to compounds involved in steroid hormone biosynthesis, potentially influencing male reproductive functions. Despite its ethnomedicinal relevance, limited research has investigated the effects of Libyan B. aegyptiaca on steroid hormone modulation in male rabbits. This study aimed to evaluate the effects of Libyan B. aegyptiaca extract on steroid hormone levels, including testosterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH), estrogen, and cortisol in male rabbits. Ripe fruits of B. aegyptiaca were collected from the Sebha region of southwest Libya, authenticated by a botany expert, and processed into a fine powder. Twenty healthy male rabbits were randomly assigned to four groups (n=5). The treatment group received 100 mg/kg body weight of B. aegyptiaca extract orally every other day for six weeks, while the control group received distilled water. Serum hormone levels were measured using ELISA kits. Statistical analysis was performed using ANOVA followed by Tukey’s multiple comparison test, with significance set at P < 0.05. Administration of B. aegyptiaca extract significantly increased plasma testosterone (2.158 ± 0.037 ng/L vs. 1.627 ± 0.077 ng/L) and LH levels (0.856 ± 0.005 mIU/ml vs. 0.780 ± 0.017 mIU/ml) compared to controls (p < 0.05). FSH showed a non-significant upward trend. Estrogen (27.415 ± 0.111 pg/ml vs. 28.691 ± 0.361 pg/ml) and cortisol (49.70 ± 3.487 ng/ml vs. 59.92 ± 1.244 ng/ml) levels were significantly reduced in treated rabbits (p < 0.05), suggesting adaptogenic and anti-stress effects. These hormonal changes indicate that B. aegyptiaca may positively modulate the hypothalamic-pituitary-gonadal (HPG) axis and stress-related endocrine pathways.